Analisis Kemampuan Membaca Permulaan pada Peserta Didik Kelas II SD Negeri 59 Sungai Raya - Nurjannah, Nurjannah; Afryaningsih, Yunika; Fatmawati, Risdiana Andika (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the early reading abilities of second-grade students at SD Negeri 59 Sungai Raya, which includes the stages of recognising letters, reading words, reading meaningless words, reading fluency and reading comprehension, and listening skills. The study used a qualitative descriptive method with data obtained through the Early Grade Reading Assessment (EGRA) test and interviews. The results show that the students' early reading skills still vary. Some students are able to recognise letters well, but others still have difficulty distinguishing between letters with similar sounds, such as ‘F’ and “V”, and have difficulty pronouncing diphthongs such as ‘NY’. In terms of reading aloud, some students still read by spelling and are not yet fluent, which affects their comprehension of the reading material. Listening skills also varied, with some students unable to answer questions related to the story because they did not understand or were not focused while listening. In addition, one student showed signs of instability that affected their attention and overall learning ability. In general, the results of the study emphasised the need for continuous reading practice, structured phonics learning, and an individualised mentoring approach so that students' early reading skills could improve optimally.